Validity of Application-Assisted Project-Based Learning Liveworksheet on Linear Program Material - Endah Oktaviana; Zulfitri Aima; Ramadoni (Department of Mathematics, Universitas Negeri Padang (UNP), 2023)
The lack of use of technology and communication in the process of learning mathematics and the teaching materials used are still not able to guide students in the learning process. The purpose of this research is to develop an Application-Assisted Project Based Learning (PjBL)-based electronic live worksheet (E-LKPD) with the assistance of a live worksheet application on valid Class X Linear Program material. This type of research is the development of the Plomp model. The instruments used were interview guidelines and questionnaires. The technique of analyzing the data is qualitative and quantitative analysis. The results of the research are the assessments made by mathematicians, namely 92.1% (very valid). The results of the assessment carried out by technology experts were 94.4% (very valid). It is concluded that E-LKPD Based on Project Based Learning Assisted by Liveworksheet Application is very valid and feasible for use by teachers and students.